A Rare Instance of Levofloxacin Induced Myoclonus - Kunder, Sushil Kiran (J Clin Diagn Res, 2017)
Levofloxacin is a widely used fluoroquinolone, mainly as a respiratory antimicrobial agent. It is employed as a second line therapeutic modality in pulmonary tuberculosis as well. The drug has been in use for ages, and is known to be both efficacious and safe. However, it is not free of adverse effects. The most dangerous ones are those involving the Central Nervous System (CNS). Although rare, levofloxacin can cause involuntary movements like chorea and myoclonus. Here by, we present a case of an elderly male patient who developed reversible myoclonus/chorea after a course of levofloxacin (which was initiated as part of his anti-tubercular therapy) following the development of peripheral neuropathy secondary to isoniazid.